Evaluación de la desmineralización química de semiantracitas provenientes de minas ubicadas en Boyacá y Santander (Colombia) (2019)
Introduction− The non-energy use of high-range carbons (anthracite) has great potential in industries such as metallurgy and in the synthesis of new carbonaceous materials. However, before being used in these applications, they must be treated to remove impurities or unwanted compounds. Objective− To evaluate the efficiency of the process of chemical demineralization of semianthracites through the use of different acids varying the operating conditions of the process. Method− Two samples were chemically characterized: Boavita (B) and Capitanejo (C) from the Boyacá and Santander (Colombia) mines, respectively. Ash and mineral matter removal from the samples was evaluated using [HCl] = 5M, HF 40% and HCl 38% at two different reaction times (45 and 60 minutes) and two particle sizes of the material (250 and 500 µm). Results− The minimum values of ash content (bs) reached through the demineralization process for samples B and C, were 0.65 and 0.76% respectively, which were obtained with a particle size of 250 µm and 60 minutes of exposure in each of the acids used in this study. Conclusions− A smaller particle size increases the contact surface and improves the degree of demineralization, regardless of the time of exposure to acids. The efficiency of the chemical benefit shows yields in the reduction of silicates, aluminates and aluminosilicates to 100%, while for ferric minerals it is above 50%.